L2 Processing of Words Containing English /æ/-/ɛ/ and /l/-/ɹ/ Contrasts, and the Uses and Limits of the Auditory Lexical Decision Task for Understanding the Locus of Difficulty - Barrios, Shannon; Hayes-Harb, Rachel (Frontiers in Communication, 2021)
Second language (L2) learners often exhibit difficulty perceiving novel phonological contrasts and/or using them to distinguish similar-sounding words. The auditory lexical decision (LD) task has emerged as a promising method to elicit the asymmetries in lexical processing performance that help to identify the locus of learners’ difficulty. However, LD tasks have been implemented and interpreted variably in the literature, complicating their utility in distinguishing between cases where learners’ difficulty lies at the level of perceptual and/or lexical coding. Building on work by Darcy et al. (2013), we elaborate a set of LD ordinal accuracy predictions associated with various logically possible scenarios concerning the locus of learner difficulty, and provide new LD data involving multiple contrasts and native language (L1) groups. The inclusion of a native speaker control group allows us to isolate which patterns are unique to L2 learners, and the combination of multiple contrasts and L1 groups allows us to elicit evidence of various scenarios. We present findings of an experiment where native English, Korean, and Mandarin speakers completed an LD task that probed the robustness of listeners’ phonological representations of the English /æ/-/ɛ/ and /l/-/ɹ/ contrasts. Words contained the target phonemes, and nonwords were created by replacing the target phoneme with its counterpart (e.g., lecture/*[ɹ]ecture, battle/*b[ɛ]ttle). For the /æ/-/ɛ/ contrast, all three groups exhibited the same pattern of accuracy: near-ceiling acceptance of words and an asymmetric pattern of responses to nonwords, with higher accuracy for nonwords containing [æ] than [ɛ]. For the /l/-/ɹ/ contrast, we found three distinct accuracy patterns: native English speakers’ performance was highly accurate and symmetric for words and nonwords, native Mandarin speakers exhibited asymmetries favoring [l] items for words and nonwords (interpreted as evidence that they experienced difficulty at the perceptual coding level), and native Korean speakers exhibited asymmetries in opposite directions for words (favoring [l]) and nonwords (favoring [ɹ]; evidence of difficulty at the lexical coding level). Our findings suggest that the auditory LD task holds promise for determining the locus of learners’ difficulty with L2 contrasts; however, we raise several issues requiring attention to maximize its utility in investigating L2 phonolexical processing.